Tissue apoptosis in mice infected with Leptospira interrogans serovar Icterohaemorrhagiae - Marinho, Márcia [UNESP] (2015)
This investigation aimed to evaluate the occurrence of some apoptotic features induced by Leptospira interrogans serovar Icterohaemorrhagiae infection in young BALB/c mice during 2, 4, 7, 10, 14 and 21 days post-infection (dpi). The animals were euthanized and lung, liver and kidneys were harvested to histopathology analysis and immunohistochemistry to caspase-3 antigen detection was performed. Chromatin condensation in kidney and liver tissues, but not in lung tissue, was observed. Caspase-3 reactive cells, mainly characterized as renal epithelial cells, were detected in the days 14 and 21 at high levels when compared to days 2, 4 and 7 (p = 0.025; p < 0.05). Lung sections revealed caspase-3 labeled alveolar cells in 10 and 14 days post-infection was higher than observed at 7 days (p = 0.0497; p < 0.05). Liver sections demonstrated reactive cells at a highest level at 14 and 21 days post-infection when comparison to 2, 4, 7 and 10 days (p = 0.0069; p < 0.05). Our results suggest that infection of L. interrogans induce in kidney, liver and lung an activation of apoptosis mediated by caspase-3 dependent pathway in later phases of infectious process.